Ready for Robot Assistance? Exploring Gender Influences on Service Robot Adoption in Luxury vs. Economy Hotels - Lee, HyeRyeon; Ma, Han; Xiao, Ge (Journal of Marketing Development and Competitiveness, 2023)
The hospitality and service industries have rapidly integrated advanced robotics and artificial intelligence (AI) to elevate guest service, assist human staff, and provide unique experiences. During the COVID-19 pandemic, this trend accelerated as hotels particularly adopted technology-oriented services to meet stringent health and safety standards. Despite the evolution of consumption behaviors and preferences, a gap remains in understanding guests’ service preferences, specifically concerning the acceptance of service robots in the post pandemic hotel sector. In response, this study examines the role of gender in adopting service robots following the COVID-19 pandemic. The findings indicate that different hotel segments influence guests’ attitudes toward service robot adoption. Furthermore, the pandemic has shifted the perceptions of female hotel guests regarding service robots, making them more receptive to such services in luxury hotels, particularly when there are pronounced health and safety concerns.